Highly Interconnected Porous Electrodes for Dye-Sensitized Solar Cells Using Viruses as a Sacrificial Template - Lee, Yong Man; Kim, Young Hun; Lee, Jun Haeng; Park, Jong Hyeok; Park, Nam-Gyu; Choe, Woo-Seok; Ko, Min Jae; Yoo, Pil J. (WILEY-V C H VERLAG GMBH, 2011)
A novel means of generating highly interconnected and nano-channeled photoelectrodes by employing one-dimensionally shaped M13 viruses as a sacrificial template is proposed for highly efficient dye-sensitized solar cells (DSSCs). The electrostatic binding between oppositely charged TiO2 nanoparticles and M13 viruses provides a uniform complexation and suppresses random aggregation of TiO2 nanoparticles. After the calcination process, the traces of viruses leave porously interconnected channel structures inside TiO2 nanoparticles, providing efficient paths for electrolyte contact as well as increased surface sites for dye adsorption. As a result, DSSCs generated using a sacrifi cialvirus template exhibit an enhanced current density (J(SC)) of 12.35 mA cm(-2) and a high photoconversion efficiency (eta) of 6.32%, greater than those of conventional photoelectrodes made of TiO2 nanoparticles (J(SC) of 8.91 mA cm(-2) and. of 4.67%). In addition, the stiffness and shape of the M13 virus can be varied, emphasizing the usefulness of the one-dimensional structural characteristics of M13 viruses for the highly interconnected porous structure of DSSC photoelectrodes.
Keywords: TIO2 NANOTUBE ARRAYS; NANOCRYSTALLINE TIO2; ELECTRICAL-IMPEDANCE; CHARGE-TRANSPORT; LIGHT; EFFICIENCY; CONVERSION; POROSITY; GROWTH; BACTERIOPHAGE